Gender in “Our Arabic Language” Books for the First Three Grades in Jordan - Khitam Ahmad Bani Omar (European Scientific Journal, ESJ, 2018)
This paper focuses on identifying the reality of gender in “our Arabic language” books for the first three grades in Jordan. To achieve the objective of the study, we made use of the descriptive analytical method. Also, we represented the study community in “our Arabic language” books for the first three grades in Jordan. In this study, various tools for analysis have been developed and verified. After the analysis has been verified, the results of the study show that the Committee for the writing of Arabic language books for the first three grades had majority of females. The authoring team and the review team were mostly male. It showed that the total number of repeated gender-related words (males) reached 922 and 70.87% in total. The gender gap (females) reached 379 (29.13%). The total number of gender-related images (males) was 250 (71.43%) based on the total number of photographs. Gender images (females) reached 100 and 28.57% of the total number of images. The total number of gender-related addresses (males) reached 8 by 16.67% of the total number of addresses. The gender-related titles were 2 and 4.17% of the total number of addresses, and 38 by 79.16% for the general addresses based on the total number of addresses. The analysis of gender roles showed that the occupations practiced by women are limited to 6 occupations, with the most prominent being a nurse and a teacher. The professions which were related to males are 20 professions, most notably pilot, fisherman, and farmer. It showed that creativity and innovation, health roles, heroism, courage, and ownership of property are limited to males without females. In regards to social roles, males can be seen as father, uncle, brother, grandfather and cousin, while the female can be seen as mother, grandmother, and aunt. The results showed a more male role than female roles.